Fatherhood: Islamic Psychology and Child Education - Wilrahmi Izati; Vebionita Megi Putri; Hilmi Hilmi (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
Parents are role models and role models for children. They will follow what their parents do. The role of both parents is very meaningful to them. The role of a father or fatherhood It is very important because, without a balance between the roles of mother and father, it is feared that children will not grow up according to our expectations. This research uses a qualitative method with a thematic analysis approach. The role of the father is indeed crucial for the growth of a child considering that many fathers do not want to be involved and think that the child's affairs are the mother's business. In Islam, the relationship between father and son even receives such beautiful attention. In the Quran, the name of a father is included as the name of one of the letters, Luqman. A father figure is included in the Al-Quran because of his expertise in educating children. By knowing the concept of the father's role, parents can carry out their role properly for the sake of their child's development and education.